Psychological stress has no association with salivary levels of β-defensin 2 and β-defensin 3 - De Brito Penna Forte, Lilibeth Ferraz; Cortelli, Sheila Cavalca; Cortelli, José Roberto; Aquino, Davi Romeiro; De Campos, Maria Valéria Costa; Cogo, Karina; Costa, Fernando Oliveira; Franco, Gilson Cesar Nobre (Journal of oral pathology & medicine, 2010)
J Oral Pathol Med (2010) 39: 765–769 Background:  Recent studies suggest that stress can predispose an individual to the development of periodontal disease, but the exact biological mechanism is unknown. Considering that psychological stress can down‐regulate the production of β‐defensins (antimicrobial peptides produced in the oral cavity), the aim of the present study was to evaluate the association between stress and salivary levels of β‐defensin 2 (HBD‐2) and β‐defensin 3 (HBD‐3). Methods:  For this purpose, seventy five volunteers, classified as periodontally healthy, were submitted to a psychological evaluation using a validated questionnaire (Questionnaire of Lipp‐ISS). Following analysis of the questionnaires, the subjects were divided in two groups (Group A: Absence of stress and Group B: Presence of stress). Unstimulated saliva samples were collected and the concentration of total protein was determined using the BCA method, and the concentrations of HBD‐2 and HBD‐3 were determined by ELISA. Results:  The levels of total protein did not show a statistically significant difference between the groups. Analyses of HBD‐2 and HBD‐3 concentrations indicate that the stress condition was not associated with the levels of either peptide in saliva (P = 0.3664 for HBD‐2 and P = 0.3608 for HBD‐3). Conclusion:  In periodontally healthy subjects, HBD‐2 and HBD‐3 levels are not influenced by stress.